Serum soluble receptor of advanced glycation end products and risk of metabolic syndrome in Egyptian obese women - Zaki, Moushira (EXCLI J, 2017)
Obesity is one of the diagnostic criteria of metabolic syndrome (MS). It is correlated with insulin resistance (IR) and high vascular risk as well. Advanced glycation end products (AGEs) and their receptor (RAGE) play an important role in abnormal metabolic components in obese women. This study aimed to explore the serum levels of sRAGE in Egyptian obese women and compare with healthy non-obese controls and investigate the relationship between serum sRAGE, metabolic parameters, and obesity complications. The soluble form of receptor for advanced glycation end products (sRAGE), anthropometry, metabolic and biochemical biomarkers were measured in 100 obese women and 100 age-matched healthy control non-obese women. The homeostasis model assessment estimate of insulin resistance (HOMA-IR) has been determined from serum insulin and glucose values. Serum sRAGE levels were significantly lower in obese cases than controls and inversely correlated with obesity and metabolic parameters. Results of univariate and multivariate analyses for determinants of serum sRAGE levels in obese cases showed that parameters statistically and significantly related were body mass index (BMI), waist circumference (WC), LDL-C, TG, BP, HOMA-IR, ALT and AST. sRAGE is a novel biomarker for metabolic dysfunction in Egyptian obese women and might predict the future cardio-metabolic events.